Tracing the Influence of Emotion Regulation on Psychological Well-Being in Psychology Students of UNP Class of 2021 - Duri, Rani Rafika; Rahmi, Kartika Aulia; Rahmadini, Yuli; Yani, Amalia Kartika; Apriyani, Apriyani; Gowasa, Maria Weni (Jurnal Psikologi Terapan, 2024)
The high academic demands faced by university students often result in psychological pressure that can affect their well-being. Psychological Well-Being (PWB) refers to an individual's psychological state that includes self-acceptance, positive relationships with others, autonomy, environmental mastery, a clear purpose in life, and continuous personal growth. One important factor influencing PWB is emotion regulation, which is an individual's ability to manage, control, and adjust their emotions according to situational demands. This study aims to examine the effect of emotion regulation on the Psychological Well-Being of psychology students at Universitas Negeri Padang, class of 2021. A quantitative research design with a correlational approach was employed, involving 165 participants selected through purposive sampling. Data were collected using a questionnaire consisting of the Emotion Regulation Scale and the Psychological Well-Being Scale. The results of simple regression analysis indicate that emotion regulation significantly influences Psychological Well-Being, contributing substantially to students' overall well-being. Most students were categorized as having moderate levels of both emotion regulation and Psychological Well-Being. These findings confirm previous research suggesting that individuals with good emotion regulation tend to have higher Psychological Well-Being. The study highlights the importance of developing effective emotion regulation strategies for students to enhance their Psychological Well-Being. The results imply that higher education institutions should implement support programs that help students manage emotions adaptively to improve their academic and personal well-being.